High-Affinity Detection of Alpha-Synuclein by Aptamer-Gold Conjugates on an Amine-Modified Dielectric Surface - Xuemei You; Subash C. B. Gopinath; Thangavel Lakshmipriya; Dingan Li (Journal of Analytical Methods in Chemistry)
Parkinson’s disease (PD) is a progressive health issue and influences an increasingly larger number of people, especially at older ages, affecting the central nervous system (CNS). Alpha-synuclein is a biomarker closely correlated with the CNS and PD. The loss of neuronal cells in the substantia nigra leads to the aggregation of alpha-synuclein in the form of Lewy bodies, and Lewy neuritis is a neuropathological hallmark. The therapeutic approach of PD focuses on alpha-synuclein as an important substrate of PD pathology. So far, research has focused on antialpha-synuclein to minimize the burden of extracellular alpha-synuclein in the brain, and as a consequence, it ameliorates inflammation. Interdigitated electrode (IDE) biosensors are efficient tools for detecting various analytes and were chosen in this study to detect alpha-synuclein on amine-modified surfaces by using antiaptamer-alpha-synuclein as the probe. In addition, a gold nanoparticle-conjugated aptamer was used to enhance the detection limit. The limit of detection for the binding between alpha-synuclein and aptamer was found to be 10 pM. Control experiments were performed with two closely related proteins, amyloid-beta and tau, to reveal the specificity; the results show that the aptamer only recognized alpha-synuclein. The proposed strategy helps to identify the binding of aptamer and alpha-synuclein and provides a possible method to lower alpha-synuclein levels and inflammation in PD patients.